2020
DOI: 10.1021/acsapm.9b01207
|View full text |Cite
|
Sign up to set email alerts
|

Increased Chemical Stability of Vapor-Phase Infiltrated AlOx–Poly(methyl methacrylate) Hybrid Materials

Abstract: Vapor-phase infiltration (VPI) transforms polymers into unique organic−inorganic hybrid materials with properties that differ from the parent polymer. Here, hybrid materials created by the infiltration of poly(methyl methacrylate) (PMMA) with trimethylaluminum (TMA) exhibit enhanced chemical stability when immersed in various solvents including toluene, cyclohexanone, and tetrahydrofuran that normally dissolve the parent PMMA. While all AlO x −PMMA hybrid materials show enhanced stability compared to the paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 31 publications
3
62
2
Order By: Relevance
“…These values are within the same order of magnitude as effective diffusivity values reported for infiltration of trimethylaluminum into poly(methyl methacrylate) 28 and can give valuable information about infiltration depth when upscaling the process to thicker films or macroscopic objects. 8,28 Diffusivity values in the order of 10 À6 cm 2 s À1 have been reported for the diffusion of gas molecules such as O 2 , N 2 , or CO 2 in (vulcanized) natural rubber, i.e. 8 orders of magnitude higher than the current findings; however, it was shown that the diffusivity rapidly decreases with increasing gas molecule size for natural rubber and other polymers.…”
Section: Paper Materials Advancescontrasting
confidence: 76%
See 3 more Smart Citations
“…These values are within the same order of magnitude as effective diffusivity values reported for infiltration of trimethylaluminum into poly(methyl methacrylate) 28 and can give valuable information about infiltration depth when upscaling the process to thicker films or macroscopic objects. 8,28 Diffusivity values in the order of 10 À6 cm 2 s À1 have been reported for the diffusion of gas molecules such as O 2 , N 2 , or CO 2 in (vulcanized) natural rubber, i.e. 8 orders of magnitude higher than the current findings; however, it was shown that the diffusivity rapidly decreases with increasing gas molecule size for natural rubber and other polymers.…”
Section: Paper Materials Advancescontrasting
confidence: 76%
“…In VPI literature, this mode has been attributed to metalorganic precursors binding to carbonyl groups, both for DEZ 32 and trimethylaluminum. 8,33,34 This suggests that DEZ entrapment is at least partially explained by binding and reaction with these carbonyl groups, which are not inherent to the pure polyisoprene structure but are rather easily created via pre-heating oxidation. This proposed mechanism is furthermore supported by the analysis of high-resolution XPS spectra of oxygen and carbon ( Fig.…”
Section: E Entrapment Of Dez Precursor In Cis-polyisoprenementioning
confidence: 99%
See 2 more Smart Citations
“…A long intermediate purge was required to remove any trapped/adsorbed water molecules from the PS surface to minimize the surface deposition of an alumina thin-film that could occur from subsequent infiltration cycles. [30,31] We note that this procedure could also be performed directly on a PS-coated monolithic silicon substrate, but for disc particles larger than ≈1 μm, limited lateral infiltration distance results in an uneven coating on the bottom surface (see Supporting Information for discussion).…”
mentioning
confidence: 99%